PERANCANGAN MOTIF BATIK TULIS KONTEMPORER UNTUK DIAPLIKASIKAN PADA COVID COVER KIT - Mira Evita; Felix Ari Dartono (Institut Seni Indonesia Surakarta, 2022)
This research is based on research data that has been carried out by Nuniek Mawardi as a consultant for Indonesia Trend Forecasting (ITF), during this pandemic period everyone is affected, directly or indirectly, so there needs to be innovative thinking to create new products that society needs today. One of them is innovating to redesign the Covid cover kit. The purpose of this research is to realize a contemporary patterned Covid cover kit with batik tulis with the theme of the 3M movement. The design method for the Covid cover kit starts with collecting references for various kinds of similar products on the market through field observations and online shop surveys. Furthermore, conducting a series of trials consisting of material testing, sewing technique trials, and visual trials. The results of this study can be concluded several things: (1) The Covid cover kit consisting of masks, gloves, and coats has a function to protect the wearer from Covid-19 when traveling and make the wearer look attractive or fashionable. (2) The process of creating and visualizing 3M themed batik is the same as the process of batik tulis in general and using the colet technique, but the motif focuses on visualizing the Covid-19 and human characters related to the 3M movement. (3) The impact of testing of materials and sewing techniques, especially on the batik coating material used, has an effect on the consideration of the application of motifs on the Covid cover kit.